PELAKSANAAN PASTORAL CARE OLEH PERAWAT DI RUANGAN INTENSIVE CARE UNIT RUMAH SAKIT ELISABETH MEDAN TAHUN 2019 - Connie Sianipar (Mitra prima, 2021)
Introduction:Pastoral care activities to actualize the love of God in the life of the faith community. The problem in this case is the large number of pastoral care that has not been well implemented in the hospital, in this case it is important to be carried out as motivated, provide comfort, feel supportive, relax, calm and peaceful because it can reduce anxiety and anxiety in dealing with internal pain healing process. Aim: this study aim to determine the implementation of pastoral care by nurses in the trigger room of Elisabeth Medan Hospital in 2019. Method: the type of research used is descriptive research with the type of cross sectional approach. The population in this study were 30 nurses in the ICU room at Elisabeth Medan Hospital. The sampling technique uses total sampling. The results of this study in the implementation of pastoral care by nurses in the trigger room were both 80% (24 nurses), enough 16% (5 nurses) and less carried out were 4% (1 nusres). Conclusion: the implementation of pastoral care by nurses in the trigger room of Elisabeth Medan Hospital was well implemented, with activities carried out by nurses such as religious assistance, spiritual assistance, pastoral counseling, sick people's visits and mentoring. From the implementation of pastoral care, the role of health workers or nurses is very important in implementing pastoral care for healing, sustaining, guiding and reconciling.